The Analysis of Experiment Video on Cognitive Conflict-Based Teaching Materials to Enhance Momentum-Impulse Concepts Understanding - Mufit, Fatni; Fitri, Atikah Dian (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2022)
Video analysis experiments can be used to construct physics concepts and equations. Integrating video analysis experiments into cognitive conflict learning allows students to increase their understanding of concepts. Some research results show that students need clarification about momentum and impulse material, low conceptual understanding, and misconceptions occur. The problem of misconceptions can hinder student learning progress. One solution to overcome these problems is the application of physics teaching materials based on cognitive conflict integrated with real experiment video analysis. This study aims to analyze the effectiveness of these teaching materials in improving students’ understanding of the concept of momentum and impulse. This study used a quasi-experimental method with a nonequivalent control group design. The sample consisted of 72 high school students with two sample classes, the experimental and the control classes, which were selected using the cluster random sampling technique. The instrument in this study was a concept test that was valid and reliable. Data were analyzed using Mann-Whitney test nonparametric statistics with the help of IBM SPSS Statistic 25. The results obtained by Sig. Asim < 0.05, in the rejection area of H0, means that teaching materials influence students’ understanding of concepts on momentum and impulse. Thus, conflict-based teaching materials integrating real experiment video analysis have been effective in increasing students’ conceptual understanding.